Lung function in insulation workers. Issue 3 (March 1993) - Clausen, J; Netterstrøm, B; Wolff, C
Abstract : To evaluate the effects of working with modern insulation materials (rock and glass wool), the members of the Copenhagen Union of Insulation Workers were invited to participate in a study based on a health examination that included lung function tests. Three hundred and forty men (74%) agreed to participate, and 166 bus drivers served as the control group. Age distribution, height, and smoking habits were similar in the two groups. Forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) were used as tests for lung function. There were no differences in FVC between the study and control groups, but the insulation workers had significantly lower values of FEV1 (mean 2.51) compared with the controls (mean 3.4 1), independent of smoking habits. Six years before the present study, 114 of the insulation workers participated in a similar study, and eight years after the initial study, the lung function of 59 of the bus drivers was tested. The decline in FVC in insulation workers who smoked was significantly higher (7.7 cl/year) than in bus drivers who smoked (3.1 cl/year); the decline in FEV1 was significantly higher in insulation workers independent of smoking habits (17.0 cl/year v 2.9 cl/year). Self assessed former exposure to asbestos was not associated with lung function in insulation workers. The study concludes that working with modern insulation materials is associated with increased risk of developing obstructive lung disease.